2016
DOI: 10.1089/jpm.2015.0334
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Feasibility Intervention to Increase Advance Care Planning among African Americans in the Deep South

Abstract: Feasibility data revealed successful implementation of a brief intervention to increase ACP engagement and willingness to complete an AD among southern African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 28 publications
3
60
0
Order By: Relevance
“…A recent study demonstrated an online patient-centered platform (PREPARE) that provides communication and decisionmaking training might increase likelihood of ACP among non-white older adults [63]; similarly, implementation of a personal health record tool resulted in increased ACP documentation rates in this population [64]. Recently, Huang and colleagues documented that motivational interviewing techniques increased ACP documentation among African Americans in the south [65]. In their randomized control trial, intervention participants received a one-time 90-min intervention, during which client-centered motivational techniques were used to enhance awareness and engagement with ACP documentation [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated an online patient-centered platform (PREPARE) that provides communication and decisionmaking training might increase likelihood of ACP among non-white older adults [63]; similarly, implementation of a personal health record tool resulted in increased ACP documentation rates in this population [64]. Recently, Huang and colleagues documented that motivational interviewing techniques increased ACP documentation among African Americans in the south [65]. In their randomized control trial, intervention participants received a one-time 90-min intervention, during which client-centered motivational techniques were used to enhance awareness and engagement with ACP documentation [65].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Huang and colleagues documented that motivational interviewing techniques increased ACP documentation among African Americans in the south [65]. In their randomized control trial, intervention participants received a one-time 90-min intervention, during which client-centered motivational techniques were used to enhance awareness and engagement with ACP documentation [65]. Future interventions should evaluate this approach among older African Americans in urban settings such as Baltimore City.…”
Section: Discussionmentioning
confidence: 99%
“…41 Health care teams should therefore tailor advance care planning conversations to account for these cultural, educational and social support differences to effectively engage minority populations in the advance care planning process. 42 For example, Song et al randomized an advance care planning intervention among Black and White hemodialysis patients and their surrogates. 43 Specifically, the intervention aimed to discern the emotional and spiritual beliefs that patients and family members had in relation to the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Respecting Choices have shown an increase in the prevalence of advance directives, greater patient-surrogate congruence for treatment preferences, receipt of goal-concordant care, and decrease in health care utilization. [21][22][23][24] A recent systematic review of Respecting Choices and related models noted limitations in research methods and inconsistency in findings related to ACP outcomes across published studies. 25 In addition, evidence on its use and outcomes in minority populations is limited.…”
Section: Interventionmentioning
confidence: 99%
“…25 In addition, evidence on its use and outcomes in minority populations is limited. 21,22 The Respecting Choices model includes three stages of ACP, First Steps, Next Steps, and Last Steps. First Steps is intended for those who have not planned.…”
Section: Interventionmentioning
confidence: 99%